2005
DOI: 10.1121/1.1993128
|View full text |Cite
|
Sign up to set email alerts
|

The effects of high presentation levels on consonant feature transmission

Abstract: The effect of high speech presentation levels on consonant recognition and feature transmission was assessed in eight participants with normal hearing. Consonant recognition in noise (0 dB signal-to-noise ratio) was measured at five overall speech levels ranging from 65 to 100 dB SPL. Consistent with the work of others, overall percent correct performance decreased as the presentation level of speech increased [e.g., G. A. Studebaker, R. L. Sherbecoe, D. M. McDaniel, and C. A. Gwaltney, J. Acoust. Soc. Am. 105… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Given that the perceptual consequences of changes in frequency selectivity at higher levels relate primarily to the use of spectral and not temporal information, it is unlikely that these changes can explain declines in recognition of speech that has been processed to preserve envelope information while minimizing spectral cues. For example, Hornsby et al (2005) analyzed changes in information transmitted for unprocessed speech presented at 65-100 dB SPL, focusing on distortion of spectral cues. In contrast to results of feature analyses in the current study, the voicing feature was most resistant, and the place feature was among the most susceptible to the effects of increasing speech level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that the perceptual consequences of changes in frequency selectivity at higher levels relate primarily to the use of spectral and not temporal information, it is unlikely that these changes can explain declines in recognition of speech that has been processed to preserve envelope information while minimizing spectral cues. For example, Hornsby et al (2005) analyzed changes in information transmitted for unprocessed speech presented at 65-100 dB SPL, focusing on distortion of spectral cues. In contrast to results of feature analyses in the current study, the voicing feature was most resistant, and the place feature was among the most susceptible to the effects of increasing speech level.…”
Section: Discussionmentioning
confidence: 99%
“…Few data are available describing level-dependent changes in feature transmission, especially when SNR and speech audibility are held constant. Hornsby et al (2005) examined confusion matrices for 22 unprocessed CV syllables presented in speech-shaped noise at overall levels from 65 to 100 dB SPL. They found that higher signal levels had the greatest negative effect on the features of duration and place of articulation.…”
Section: Acoustic-phonetic Features In Noise-vocoded Consonantsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a main effect of signal level is consistent with the perceptionin-noise literature. Sentence, word, and syllable perception has been shown to get worse at high signal levels (clinically referred to as rollover) in quiet and in background noise, and the magnitude of the performance decrement at high signal levels is modulated by other factors, such as SNR, noise spectrum, and noise bandwidth (Molis and Summers 2003;Hornsby et al 2005;Studebaker et al 1999;Summers and Molis 2004). In the current study, the signal level effects found in the literature were replicated; decrements in this study occurred above 60 dB, primarily at the 70-and 80-dB signal levels.…”
Section: Behaviormentioning
confidence: 99%
“…The auditory image model proposed by Patterson and colleagues (e.g., Akeroyd and Patterson 1995;Patterson 1994), which incorporates adaptive threshold tracking, or adaptation to the background temporal envelope level of an ongoing stimulus, also demonstrates the potential importance of SNR. Several psychophysical studies also indicate that signal level plays an important role in perception in noise by demonstrating that signal level has a small but significant effect on accuracy when SNR is held constant (Summers and Molis 2004;Studebaker et al 1999;Hornsby et al 2005). In contrast, signal level was not a significant contributor to cortical-level processing (Billings et al 2009).…”
Section: Introductionmentioning
confidence: 98%